2021
DOI: 10.3390/jcm10132798
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Depressive Symptoms, Anxiety, and Somatization Symptoms in Male and Female Patients with Chronic Tinnitus

Abstract: Objective: To investigate the joint impact of tinnitus-related distress (TRD), anxiety, depressive symptoms, and other somatization symptoms on health-related quality of life (HRQoL) in female vs. male patients with chronic tinnitus. Method: Three-hundred-and-fifty-two patients with chronic tinnitus completed audiological testing and a psychological assessment battery that comprised—among other measures—German versions of the Tinnitus Questionnaire, Hospital Anxiety and Depression Scale, Somatic Symptom Scale-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 95 publications
2
24
0
2
Order By: Relevance
“…These results extend our understanding of the association among the severity of ARHL (8,9), tinnitus (10,18), physical frailty (13,14,26), and the presence of ARHL and/or tinnitus (17) with HRQoL. Furthermore, these findings provide more evidence on the interaction among ARHL, tinnitus, and physical frailty in their relationship with HRQoL after adjusting for demographic, health-related, and psychosocial factors.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…These results extend our understanding of the association among the severity of ARHL (8,9), tinnitus (10,18), physical frailty (13,14,26), and the presence of ARHL and/or tinnitus (17) with HRQoL. Furthermore, these findings provide more evidence on the interaction among ARHL, tinnitus, and physical frailty in their relationship with HRQoL after adjusting for demographic, health-related, and psychosocial factors.…”
Section: Discussionsupporting
confidence: 73%
“…Physical frailty coexisting with ARHL, tinnitus, and ARHL with tinnitus had a stronger effect on the overall HRQoL. Several previous studies have indicated that ARHL ( 8 , 9 , 28 , 29 ) and/or tinnitus ( 10 , 30 ) were negatively associated with HRQoL. However, we found no significant association among ARHL severity, the presence of ARHL and/or tinnitus, and HRQoL, and the association between tinnitus severity and HRQoL was also no longer significant after adjustment for psychosocial factors.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations